A dataset of nectar sugar production for flowering plants found in urban green spaces - Nicholas E. Tew; Katherine C. R. Baldock; Joanne M. Morten; Stephanie Bird; Ian P. Vaughan; Jane Memmott (Ecological Solutions and Evidence, 2023)
Abstract Nectar and pollen are floral resources that provide food for insect pollinators, so quantifying their supplies can help us to understand and mitigate pollinator declines. However, most existing datasets of floral resource measurements focus on native plants found in rural landscapes, so cannot be used effectively for estimating supplies in urban green spaces, where non‐native ornamental plants often predominate. We sampled floral nectar sugar in 225 plant taxa found in UK residential gardens and other urban green spaces, focussing on the most common species. The vast majority (94%) of our sampled taxa are non‐native, filling an important research gap and ensuring these data are also relevant outside of the United Kingdom. Our dataset includes values of daily nectar sugar production for all 225 taxa and nectar sugar concentration for around half (102) of those sampled. Nectar extraction was conducted according to published methods, ensuring our values can be combined with other datasets. We anticipate that the two main uses of these data are (1) to estimate the nectar production of habitats and landscapes and (2) to identify high‐nectar plants of conservation importance. To increase the utility of our data, we provide guidance for scaling nectar values up from single flowers to floral units, as is commonly done in field studies.